Overview of university students about causes and treatment of bacterial disease Brucellosis - Muhammad Imran Qadir; Misbah Rozi (Global Journal of Rare Diseases - Peertechz Publications, 2019)
Objective of the present study was to evaluate the overview of Brucellosis disease. Brucellosis is a bacterial disease which is also called undulant fever. Both human and animals are affected from this disease. When people eat contaminated food like raw meat and unpasteurized milk, they suffered from brucellosis disease. A Questionnaire was prepared that contain the question like Brucellosis is a bacterial disease, viral disease or a fungal disease. Are you suffered from this disease? Is Brucellosis treated by medicines or a surgery? Total number of university students, which took part in this research are 90. All the students belong to Bahauddin Zakariya University in Multan, Pakistan age from 20-23. We concluded that we should avoid raw meat and unpasteurized milk to getting the chance of Brucellosis.